POTENSI PILIHAN MENU MAKANAN CITA RASA KARO SEBAGAI DAYA TARIK WISATA KULINER DI BERASTAGI TANAH KARO - Tarigan, Nirwaty; Tambunan, Lyandru Togu Mulia (Jurnal Ilmiah Akomodasi Agung, 2024)
Research on the potential of karo-flavored food menu options as a culinary tourism attraction was carried out in Berastagi, Karo Regency, North Sumatra Province. Based on researchers' interest in the development of Karo culinary tourism which has diverse potential, starting from raw materials sourced from the natural riches of the Karo land itself, unique preparations, several Asian and Italian foods produced with Karo flavors which are currently widely served on restaurant food menus of the restaurants in Berastagi Tanah Karo. The expectation by the sellers or owners of the tourism attractions as well as restaurants owners are to turned the place to become one of the culinary tourism attractions and also an introduction to typical Karo food for tourists who come to visit. This research aims to find out what types of typical Karo food are, how they are processed and served, tourist attractions that are facilitated with restaurants or cafes that serve Karo food menus, and examine the development of Karo food and the potential of typical Karo menu choices as a resource. Culinary tourism attraction in Berastagi, Karo Regency. This research takes a qualitative approach. The informants are producers and sellers/restaurant owners in Berastagi, Karo district. The research location is a tourist attraction in Berastagi. Data collection was carried out using observation, interviews, and documentation techniques. The results of the research show that the potential choices of Karo flavored menus served in restaurants in Berastagi are dominated by local food ingredients, Asian food menus such as fried rice, and fried noodles, and Italian dishes such as pizza and others served with Karo flavors, including cakes. Cakes and sandwiches which are also served with Karo flavors, can create a culinary tourism attraction in Berastagi Tanah Karo.